Effect of size and surface chemistry of gold nanoparticles on their retention in a sediment-water system and Lumbriculus variegatus. Issue 12 (15th October 2021) - Luo, Ping; Ma, Guibin; Dudkiewicz, Agnieszka; Mao, Zhen; Wang, Lizhang; Jiang, Jiachao
Abstract: With the increased production, usage, and disposal of engineered nanoparticles (ENPs), there is growing concern over the fate of ENPs in the environment, their potential bioavailability and ecotoxicity. It is assumed that bioavailability and uptake into organisms depend on the environmental conditions as well as the physicochemical properties of ENPs, such as particle size or surface coating. A major sink for nanoparticles is expected to be sediments due to sorption and agglomeration processes. Accordingly, this study, investigated how different sizes (5 and 30 nm) and surface coatings of three different AuENPs based on citrate (AuCIT), mercaptoundecanoic acid (AuMUDA), and bovine serum albumin (AuBSA) affected the retention of ENPs in a sediment-water system and subsequent uptake into sediment-dwelling organism Lumbriculus variegatus ( L. variegatus ). Surface charge was found to be one of the factors affecting retention of the AuENPs in the sediment-water system. More negatively charged AuENPs had a higher mass fraction in the supernatant after 24 h exposure. Furthermore, the stability of AuENPs in the supernatant depended more on their zeta potential than particle size (5 nm vs. 30 nm). The surface coating was found to play an important role in the uptake (after depuration) of Au in L. variegatus, that is, AuBSA > AuCIT > AuMUDA.